The Role of Laparoscopy in the Management of a Diagnostic Dilemma: Jejunal Ectopic Pancreas Developing into Jejunojejunal Intussusception. (27th July 2017) - Giordano, Alessio; Alemanno, Giovanni; Bergamini, Carlo; Prosperi, Paolo; Bruscino, Alessandro; Valeri, Andrea
Abstract : Ectopic pancreas (EP) is a rare congenital anomaly defined as the presence of pancreatic tissue in topographic anomaly. It is usually silent but it may become clinically evident when complicated by acute conditions. The development of laparoscopic surgery has changed the way to manage such conditions, especially in the setting of emergency surgery, thanks to its diagnostic and therapeutic role with excellent results. We decided to perform an emergency diagnostic exploratory laparoscopy in a 29-year-old man with an acute abdomen and nonspecific radiological images for intestinal occlusion. A jejunojejunal intussusception was found, caused by a mass. We decided to carry out minilaparotomy to perform a resection of the affected jejunum. Histological examination confirmed the presence of a jejunal ectopic pancreas. Adult intussusception caused by EP represents 5% of all cases of intussusception. As CT scan, especially when performed in emergency setting for small bowel obstruction diagnosis, can usually demonstrate nondiagnostic findings suggestive of intussusception of unknown origin, laparoscopic exploration could help surgeons in order to perform a resolute diagnosis and treat the pathology.